Energy independence problem solving by biomass technologies - Shtefan, Yevgenii; Seryogin, Oleksandr (My University, 2021)
In the first third of the 21st century, the world economy has faced significant challenges in the energy sector, and biomass as an energy resource can make a significant contribution to the production of heat, electricity and biofuels. Modern leading energy companies have experience in research, development and implementation of all bioenergy technologies (including direct combustion, co-incineration, anaerobic digestion, energy production from waste), as well as experience in bioeconomics. Organizations operating in the waste sector play a key role in the transition to a circular economy. They manage a significant part of the materials’ flows and produce resources which can be re-injected into the economy, either as materials or as energy. The sector also provides an essential environmental service for our society, both from a citizens’ point of view and from the perspective of the industrial, agriculture, and service sectors. It frees every household and organization of their waste, and it reduces related risks. The main motivation for the introduction of heat generating capacity on biomass is independence from imported energy, which ensures the energy independence of the state as an important component of its political and economic independence.

У першій третині 21 століття світова економіка зіткнулася зі значними проблемами в енергетичному секторі, і біомаса як енергетичний ресурс може зробити значний внесок у виробництво тепла, електроенергії та біопалива. Сучасні провідні енергетичні компанії мають досвід дослідження, розробки та впровадження всіх біоенергетичних технологій (включаючи пряме спалювання, спільне спалювання, анаеробне зброджування, виробництво енергії з відходів), а також досвід у біоекономіці. Організації, що працюють у секторі переробки відходів, відіграють ключову роль у переході до економіки замкнутого циклу. Вони керують значною частиною потоків матеріалів і виробляють ресурси, які можуть бути повторно введені в економіку у вигляді матеріалів або енергії. Сектор також забезпечує важливу екологічну послугу для нашого суспільства як з точки зору громадян, так і з точки зору промисловості, сільського господарства та секторів послуг. Це звільняє кожне домогосподарство та організацію від сміття та зменшує відповідні ризики. Основною мотивацією впровадження теплогенеруючих потужностей на біомасі є незалежність від імпортної енергії, що забезпечує енергетичну незалежність держави як важливу складову її політичної та економічної незалежності.
Keywords: energy sector; biomass; energy independence; енергетичний сектор; біомаса; енергетична незалежність; кафедра електропостачання і енергоменеджменту